Digital Proficiency and Entrepreneurial Mindset for SME Success through Market Savvy and Tech Literacy - Wulandari, Siti Sri; Diah, Mohd Lizam Bin Mohd; Asari, Andi (Pandawan, 2025)
Micro, Small, and Medium Enterprises (MSMEs) are vital to Indonesia economy, yet many face challenges in adapting to the digital era. This study examines the impact of market orientation on business performance, with digital literacy as a potential mediator, focusing on MSMEs in Surabaya, Indonesia. Using a quantitative approach, Structural Equation Modeling (SEM) with WarpPLS was employed to analyze data from 70 MSME owners collected through questionnaires. The results demonstrate that market orientation significantly influences both digital literacy and business performance. However, digital literacy does not mediate the relationship between market orientation and business performance, suggesting that its role is direct rather than intermediary. These findings highlight the critical importance of market-oriented strategies in driving MSME success and underline the necessity for improved digital literacy to enhance competitive advantage. MSME managers are encouraged to adopt structured customer feedback mechanisms, invest in digital training programs, and leverage market monitoring tools to better adapt to dynamic market demands. By integrating market orientation with advanced digital practices, MSMEs can achieve sustainable growth and improved operational efficiency. Future research should explore other potential mediators, such as innovation capacity or organizational culture, to better understand the dynamics of MSME performance. This study provides valuable insights into how MSMEs in mid-tier urban centers can thrive in the digital era, contributing to broader discussions on entrepreneurship and digital transformation in developing economies.